2002
DOI: 10.1163/156855102753613246
|View full text |Cite
|
Sign up to set email alerts
|

Damage tolerant behaviors of a biomimetic CFRP laminate

Abstract: The present work examines the damage tolerant behaviors of synthetic composites by using composite architectures observed in biological materials. The static, impact, and compression after impact (CAI) behaviors of biomimetic CFRP laminates with stacking sequences similar to those found in animal hard tissues are compared to those of a standard quasi-isotropic and a cross-ply laminates.The dependence of the extent of damage in the samples with a hole under tensile loading on the laminate lay-up was analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Within the forewings of insects, both the laminated arrangement of the chitin fibers [Gullan & Cranstion, 1994;Leopoldj et al, 1992;Banerjee, 1988;Zelazny & Neville, 1972] and the mechanical characteristics of these equiangular laminating layers of the biomimetic composites [Tanimoto et al, 1998;Ben et al, 1998;Masuda et al, 1995] have been reported on previously. The authors have reported the presence of non-equiangular laminating structures in the forewing of A. dichotoma [Chen et al, 2001a].…”
Section: Optimal Composite Structures In the Forewings Of Beetlesmentioning
confidence: 99%
“…Within the forewings of insects, both the laminated arrangement of the chitin fibers [Gullan & Cranstion, 1994;Leopoldj et al, 1992;Banerjee, 1988;Zelazny & Neville, 1972] and the mechanical characteristics of these equiangular laminating layers of the biomimetic composites [Tanimoto et al, 1998;Ben et al, 1998;Masuda et al, 1995] have been reported on previously. The authors have reported the presence of non-equiangular laminating structures in the forewing of A. dichotoma [Chen et al, 2001a].…”
Section: Optimal Composite Structures In the Forewings Of Beetlesmentioning
confidence: 99%
“…Within the forewings of insects, both the laminated arrangement of the chitin fibers [Gullan & Cranstion, 1994;Leopoldj et al, 1992;Banerjee, 1988;Zelazny & Neville, 1972] and the mechanical characteristics of these equiangular laminating layers of the biomimetic composites [Tanimoto et al, 1998;Ben et al, 1998;Masuda et al, 1995] have been reported on previously. The authors have reported the presence of non-equiangular laminating structures in the forewing of A. dichotoma [Chen et al, 2001a].…”
Section: Optimal Composite Structures In the Forewings Of Beetlesmentioning
confidence: 99%
“…However, the forewing of the beetle has long been mistakenly classified as nonliving matter [7], and perhaps due to this oversight, its inside microstructure has drawn little attention from biologists and bionic engineers. In the literature, studies have tended to focus on the following aspects of the beetle forewing: the composition of the chitin fiber (referred to as "fiber") and proteins [5,8,9,10], the stored internal air sacs [11], the chitin fiber layers themselves, which are of helicoidal structure [5,12], the orientation of chitin fibers [4,13,14], including the constant angle of fiber orientation [15] and dual spiral structures with small holes [16], and their influence on the mechanical properties of the biomimetic composite materials [13,17 ]. However, current knowledge on biomimetic composite materials is still limited.…”
Section: Introductionmentioning
confidence: 99%